Not so unthinkable [nuclear weapons]. - Gover, J.E (IEEE spectrum)
Discusses developments which offer scenarios that, to some military strategists, would justify the use of nuclear weapons. The sorts of nuclear weapons likely to figure into war planners' recommendations are much smaller than those designed to wipe out entire cities, and they would be targeted at hardened, isolated military installations. Broadly speaking, nuclear weapons fall into two categories. Strategic weapons have explosive yields in the range of several hundred kilotons up to several megatons. Tactical weapons have much lower yields, down to a few kilotons. Strategic weapons were meant to destroy an entire city. Tactical nuclear weapons were intended for use at closer range-for example, on a battlefield, perhaps launched by a large artillery cannon.